2017
DOI: 10.1262/jrd.2016-108
|View full text |Cite
|
Sign up to set email alerts
|

Male infertility-related molecules involved in sperm-oocyte fusion

Abstract: Male infertility has become a very serious problem in the human reproduction system, but the molecular mechanism of infertility remains largely unknown. Fertilization is the phenomenon in which a sperm and oocyte find each other, interact, and fuse. Sperm-oocyte fusion-related factors on the sperm side play crucial roles in male infertility. For example, IZUMO1 is well-known as a sperm protein essential for fusion of a sperm and oocyte, but its dysfunction or mutation can result in male infertility. Recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…In this regard, although the function for BPI in FF is still unknown, the presence of BPIFA2 during the ovulatory seasons may be important to protect the female genital tract (e.g., oviduct). Also, few reports have found that BPI is expressed in the testis and epididymis of mice and appears to take part in the process of gamete interactions [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, although the function for BPI in FF is still unknown, the presence of BPIFA2 during the ovulatory seasons may be important to protect the female genital tract (e.g., oviduct). Also, few reports have found that BPI is expressed in the testis and epididymis of mice and appears to take part in the process of gamete interactions [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Disrupted or unbalanced cell fusion in developmental processes is linked to human diseases. Defects in sperm–egg fusion lead to male infertility (Mou and Xie, 2017). Impediments in myoblast fusion can be perinatally lethal in mice and have been associated with some human myopathies (Di Gioia et al, 2017; Sampath et al, 2018).…”
Section: Cell Fusion In Diseasementioning
confidence: 99%
“…Contraceptive vaccines evoke an immune response to molecules that have indispensable roles in the reproduction process. Several proteins have been used successfully to reduce the fertility of various animal species, including antigens associated with sperm [ 14 , 15 , 16 ] and oocytes [ 17 , 18 , 19 ], as well as hormones and their receptor proteins [ 20 , 21 ]. The unique specificity of sperm and oocyte proteins makes them ideal candidates for immunocontraceptive vaccines.…”
Section: Introductionmentioning
confidence: 99%